Electrophoretic deposition of carbon nanotube-ceramic nanocomposites - Boccaccini, A. R.; Cho, J.; Subhani, T.; Kaya, C.; Kaya, F. (ELSEVIER SCI LTD, 2010)
The purpose of this paper is to present an up-to-date comprehensive overview of current research progress in the development of carbon nanotube (CNT)-ceramic nanocomposites by electrophoretic deposition (EPD). Micron-sized and nanoscale ceramic particles have been combined with CNTs, both multiwalled and single-walled, using EPD for a variety of functional, structural and biomedical applications. Systems reviewed include SiO2/CNT, TiO2/CNT, MnO2/CNT, Fe3O4/CNT, hydroxyapatite (HA)/CNT and bioactive glass/CNT. EPD has been shown to be a very convenient method to manipulate and arrange CNTs from well dispersed suspensions onto conductive substrates. CNT-ceramic composite layers of thickness in the range <1-50 mu m have been produced. Sequential EPD of layered nanocomposites as well as electrophoretic co-deposition from diphasic suspensions have been investigated. A critical step for the Success of EPD is the prior functionalization of CNTs, usually by their treatment in acid solutions, in order to create functional groups on CNT surfaces so that they can be dispersed uniformly in solvents, for example water or organic media. The preparation and characterisation of stable CNT and CNT/ceramic c particle suspensions as well as relevant EPD mechanisms are discussed. Key processing stages, including functionalization of CNTs, tailoring zeta potential of CNTs and ceramic particles in Suspension as well as specific EPD parameters, such as deposition voltage and time, are discussed in terms of their influence on the quality of the developed CNT/ceramic nanocomposites. The analysis of the literature confirms that EPD is the technique of choice for the development of complex CNT-ceramic nanocomposite layers and coatings of high structural homogeneity and reproducible properties. Potential and realised applications of the resulting CNT-ceramic composite coatings are highlighted, including fuel cell and supercapacitor electrodes, field emission devices, bioelectrodes, photocatalytic films, sensors as well as a wide range of functional, structural and bioactive coatings. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Films; Suspensions; Nanocomposites; Nanotubes; Electrophoretic deposition; FIELD-EMISSION PROPERTIES; REINFORCED HYDROXYAPATITE COATINGS; COMPOSITE-MATERIALS; PHOTOCATALYTIC ACTIVITY; MATRIX COMPOSITES; THIN-FILMS; FABRICATION; TITANIUM; TIO2; NANOPARTICLES; Materials Science